Combining Song—And Speech-Based Language Teaching: An Intervention With Recently Migrated Children - Busse, Vera; Jungclaus, Jana; Roden, Ingo; Russo, Frank A.; Kreutz, Gunter (Frontiers in Psychology, 2018)
There is growing evidence that singing can have a positive effect on language learning, but few studies have explored its benefit for children who have recently migrated to a new country. In the present study, recently migrated children (N = 35) received three 40-minute sessions where all students learnt the lyrics of two songs designed to simulate language learning through alternating teaching modalities (singing and speaking). Children improved their language knowledge significantly including on tasks targeting the transfer of grammatical skills, an area largely neglected in previous studies. This improvement was sustainable over the retention interval. However, the two teaching modalities did not show differential effects on cued recall of song lyrics. Taken together, the data cautiously suggest that singing may be useful as an additional teaching strategy irrespective of initial language proficiency, warranting more research on songs as a supplement for grammar instruction.